ISU DAN CABARAN BADAN PENSIJILAN HALAL DI MALAYSIA: The Issues and Challenges of Halal Certification Bodies in Malaysia - Buang, Ahmad Hidayat; Mahmod, Zulzaidi (Jurnal Syariah, 2019)
Public confidence concerning the permissibility of a particular product or whether it is halal, particularly for Muslims, is secured through the display or label confirming halal certification issued by an authorized or recognized organization. To the producers, halal certification can be considered as a marketing tool. In Malaysia, several regulations have been put in place relating to halal certification or labelling. The main complaint pertaining to halal certification in Malaysia concerns the existence of several halal certification bodies, which has created confusion among the Muslim consumers. The aim of this article is to analyse the reasons for this confusion and to offer some practical solutions from the legal point of view. Data are collected through library research and interviews with relevant government officials. Descriptive and content analysis of the reading materials and relevant law statutes is used in the discussion. The findings from the analysis of the data collected suggest that the existing legal provisions, especially Trade Description Rules 1972, are not equipped to deal with the current issues and challenges of halal certification, especially concerning the control over halal certification bodies that offer the service of halal certification to the public. This article, to a limited extent, attempts to highlight several important developments, especially the introduction of the new Trade Descriptions Act 2011, which was not available at the time this article was written.